Islamic Radicalization through social media for ISIS Recruitment of Fighters - Desa, Mazida Mohd; Nasir, Norruzeyati; Jasni, Mohd Alif; Nordin, Mohd Norazmi; Haron, Muhd Zulhilmi; Shah, Mohd Ab Malek Md; Ismail, Albert Feisal Muhd Feisal (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper will briefly discussed on the history of ISIS establishment, their ideology and the concept of Islamic radicalization that have been disseminate through social media with the purpose of recruiting fighters, promoting jihad ideology and intimidating their enemies. This will further emphasize on the current phenomena of ISIS social media engagement as a global problem to terrorism. With the subsequent growth of social media platforms for communications, militant groups like ISIS have incorporated their ideology through social media and further employ recruitment strategy through the use of social media networks. Under the command of Abu Bakr al-Baghdadi, ISIS has established an Islamic caliphate, an advanced common jihadist ideas in a short amount of time which is an achievement that no other insurgency has been able to accomplish. The ISIS powered their projects by combining innovative technological strategies and advancing with strong force, financial resources and also intimidation as their main ideology.